Short-term clinical, functional and MRI findings after hamstring allograft vs. autograft ACL reconstruction - Paul Ruckenstuhl; Amir Koutp; Tobias Oswald; Stefan Fischerauer; Andreas Leithner; Matthias Groell; Patrick Sadoghi; Gerald Gruber; Gerwin A. Bernhardt (Wiener klinische Wochenschrift, 2026)
Summary Purpose Graft choice in primary anterior cruciate ligament (ACL) reconstruction remains controversial. While hamstring autografts are common, allografts offer advantages such as no donor site morbidity and reduced operation time. This study aimed to compare the clinical, functional and health-related quality of life (HRQOL) outcomes of hamstring allografts vs. autografts in primary ACL reconstruction. Methods In this single-center randomized controlled trial, patients undergoing primary ACL reconstruction were randomized to receive either a hamstring allograft or autograft. Clinical evaluation and patient-reported outcome measures (PROMs), including the International Knee Documentation Committee (IKDC), Knee Injury and Osteoarthritis Outcome Score (KOOS), and Short Form (SF)-36 Health survey, were collected preoperatively and at multiple follow-ups to 12 months. Operation time and postoperative magnetic resonance imaging (MRI) scans at 12 months were also analyzed. Results The final cohort included 25 patients (13 allograft, 12 autograft). At 12 months, no statistically significant differences between groups were detected for any PROM. Mean IKDC scores were 83.0 ± 7.2 in the allograft group and 87.2 ± 5.0 in the autograft group ( p = 0.12). Both groups demonstrated improvement in patient-reported functional outcomes; however, objective instrumented laxity testing was not performed. Mean operation time was significantly shorter for the allograft group (61.6 ± 11.4 min) compared to the autograft group (83.0 ± 13.6 min; p < 0.001). Conclusion In this small pilot randomized cohort of patients aged 27 years and older, no statistically significant short-term differences in PROMs were detected between hamstring allograft and autograft ACL reconstruction at 12 months. Allograft use was associated with significantly shorter operative time. These findings should be interpreted cautiously because the study was not powered to demonstrate equivalence or noninferiority and longer term follow-up with objective laxity testing is required to assess graft durability and stability.